Hospital discharge planning for Canadians experiencing homelessness. Issue 1 (1st November 2018) - Buccieri, Kristy; Oudshoorn, Abram; Frederick, Tyler; Schiff, Rebecca; Abramovich, Alex; Gaetz, Stephen; Forchuk, Cheryl
Abstract : Purpose: People experiencing homelessness are high-users of hospital care in Canada. To better understand the scope of the issue, and how these patients are discharged from hospital, a national survey of key stakeholders was conducted in 2017. The paper aims to discuss this issue. Design/methodology/approach: The Canadian Observatory on Homelessness distributed an online survey to their network of members through e-mail and social media. A sample of 660 stakeholders completed the mixed-methods survey, including those in health care, non-profit, government, law enforcement and academia. Findings: Results indicate that hospitals and homelessness sector agencies often struggle to coordinate care. The result is that these patients are usually discharged to the streets or shelters and not into housing or housing with supports. The health care and homelessness sectors in Canada are currently structured in a way that hinders collaborative transfers of patient care. The three primary and inter-related gaps raised by survey participants were: communication, privacy and systems pressures. Research limitations/implications: The findings are limited to those who voluntarily completed the survey and may indicate self-selection bias. Results are limited to professional stakeholders and do not reflect patient views. Practical implications: Identifying systems gaps from the perspective of those who work within health care and homelessness sectors is important for supporting system reforms. Originality/value: This survey was the first to collect nationwide stakeholder data on homelessness and hospital discharge in Canada. The findings help inform policy recommendations for more effective systems alignment within Canada and internationally.